2010
DOI: 10.1002/adsc.200900880
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Intramolecular Alkyne Cycloisomerization Cascade: Direct Synthesis of Aryl‐Annulated[a]carbazoles from Aniline‐Substituted Diethynylarenes

Abstract: Abstract:Aniline-substituted diethynylarenes, which are readily synthesized through Sonogashira coupling reactions from commercially available 1,2-dihaloarenes, directly produce aryl-and heteroarylannulated[a]carbazoles by the gold-catalyzed intramolecular cascade hydroamination/cycloisomerization without producing theoretical by-products. This new atom-economical route is easily applicable to various aryl-annulated[a]carbazoles containing an alkyl, aryl or ester substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…The same authors found [33] that the action of the base on 2,3-dialkynylpyridine 20 having the ortho aminophenyl substituent at the triple bond promotes another cascade transformation including the consecutive 5-endo-dig/5-exo-dig cyclizations with the pyrrole and fulvene ring closure (Scheme 14). At the same time in the presence of catalytic amounts of NaAuCl 4 ·2Н 2 O compound 20 is converted into the pyridocarbazole 22 [33,34].…”
Section: T-buomentioning
confidence: 88%
See 3 more Smart Citations
“…The same authors found [33] that the action of the base on 2,3-dialkynylpyridine 20 having the ortho aminophenyl substituent at the triple bond promotes another cascade transformation including the consecutive 5-endo-dig/5-exo-dig cyclizations with the pyrrole and fulvene ring closure (Scheme 14). At the same time in the presence of catalytic amounts of NaAuCl 4 ·2Н 2 O compound 20 is converted into the pyridocarbazole 22 [33,34].…”
Section: T-buomentioning
confidence: 88%
“…Under analogous conditions the N-methyl and N-Boc derivatives of compounds 23 are easily cyclized into N-substituted benzocarbazoles. High yields of the cyclization products are also observed when the 2,3-dialkynyl derivatives of thiophene and furan are used as substrates [33,34].…”
Section: Scheme 16mentioning
confidence: 88%
See 2 more Smart Citations
“…[14][15][16][17][18][19] Unlike many transition metal catalyzed reactions, gold catalysis does not require anhydrous and air free conditions.…”
Section: -13mentioning
confidence: 99%